5-(Sulfamoyl)thien-2-yl 1,3-oxazole inhibitors of carbonic anhydrase II with hydrophilic periphery - Stanislav Kalinin; Alexander Kovalenko; Annika Valtari; Alessio Nocentini; Maxim Gureev; Arto Urtti; Mikhail Korsakov; Claudiu T. Supuran; Mikhail Krasavin (Journal of Enzyme Inhibition and Medicinal Chemistry)
Hydrophilic derivatives of an earlier described series of carbonic anhydrase inhibitors have been designed, prepared and profiled against a panel of carbonic anhydrase isoforms, including the glaucoma-related hCA II. For all hydrophilic derivatives, computational prediction of intraocular permeability routes showed the predominance of conjunctival rather than corneal absorption. The potentially reactive primary or secondary amine periphery of these compounds makes them suitable candidates for bioconjugation to polymeric drug carriers. As was shown previously, the most active hCA II inhibitor is efficacious in alleviating intraocular pressure in normotensive rabbits with efficacy matching that of dorzolamide.